End-of-Life Practices in France under the Claeys-Leonetti Law: Report of Three Cases in the Oncology Unit - de Nonneville, Alexandre (Case Rep Oncol, 2016)
On February 2, 2016, the French government enacted the Claeys-Leonetti law introducing the right to deep and continuous sedation and forbade euthanasia for end-of-life patients. This article reports the first descriptions of this kind of intervention at the final stage of life of 3 patients and highlights the need of patient-centered goals and the importance of close collaboration between the patient, family, and medical and paramedical team to achieve a higher quality of final palliative care.